Integrated Metabolomic and Transcriptomic Analyses Reveal Novel Insights of Anthocyanin Biosynthesis on Color Formation in Cassava Tuberous Roots - Fu, Lili; Ding, Zehong; Tie, Weiwei; Yang, Jinghao; Yan, Yan; Hu, Wei (Frontiers in Nutrition, 2022)
Yellow roots are of higher nutritional quality and better appearance than white roots in cassava, a crucial tropical and subtropical root crop. In this work, two varieties with yellow and white cassava roots were selected to explore the mechanisms of color formation by using comparative metabolome and transcriptome analyses during seven developmental stages. Compared with the white-rooted cassava, anthocyanins, catechin derivatives, coumarin derivatives, and phenolic acids accumulated at higher levels in yellow-rooted cassava. Anthocyanins were particularly enriched and displayed different accumulation patterns during tuberous root development. This was confirmed by metabolic comparisons between five yellow-rooted and five white-rooted cassava accessions. The integrative metabolomic and transcriptomic analysis further revealed a coordinate regulation of 16 metabolites and 11 co-expression genes participating in anthocyanin biosynthesis, suggesting a vital role of anthocyanin biosynthesis in yellow pigmentation in cassava tuberous roots. In addition, two transcriptional factors, i.e., MeMYB5 and MeMYB42, were also identified to co-express with these anthocyanin biosynthesis genes. These findings expand our knowledge on the role of anthocyanin biosynthesis in cassava root color formation, and offer useful information for the genetic breeding of yellow-rooted cassava in the future.